2009
DOI: 10.1073/pnas.0903654106
|View full text |Cite
|
Sign up to set email alerts
|

A possible mechanism for exonuclease 1-independent eukaryotic mismatch repair

Abstract: Mismatch repair contributes to genetic stability, and inactivation of the mammalian pathway leads to tumor development. Mismatch correction occurs by an excision-repair mechanism and has been shown to depend on the 5 to 3 hydrolytic activity exonuclease 1 (Exo1) in eukaryotic cells. However, genetic and biochemical studies have indicated that one or more Exo1-independent modes of mismatch repair also exist. We have analyzed repair of nicked circular heteroduplex DNA in extracts of Exo1-deficient mouse embryo f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
155
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(167 citation statements)
references
References 20 publications
8
155
1
Order By: Relevance
“…2A). 26 Previous studies showed that hyperacetylation induced by sodium butyrate stimulates nucleotide excision repair in UVirradiated cells. 8,10,[47][48][49][50] The stimulation of DNA repair was shown to be associated with alterations in chromatin structure making damaged sites in DNA more accessible to repair enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2A). 26 Previous studies showed that hyperacetylation induced by sodium butyrate stimulates nucleotide excision repair in UVirradiated cells. 8,10,[47][48][49][50] The stimulation of DNA repair was shown to be associated with alterations in chromatin structure making damaged sites in DNA more accessible to repair enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…2A). 24,26 HCT116 cells are deficient in MMR due to defective MLH1, which likely affects formation of the MMR complex and recruitment of EXO1. 24 In these cells, we expect that nicked DNA constructs with a mismatch become primary substrates for an EXO1-independent pathway ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the 5′ nicks are formed, repair appears to occur as observed in the 5′ nickdirected MMR reactions. MMR can also occur in the absence of Exo1 (24,34,35); however, our knowledge of Exo1-independent MMR mechanisms is not as well developed as it is for Exo1-dependent MMR (19,36,37).…”
mentioning
confidence: 99%
“…To date, no such enzyme could be identified. However, it could be shown that 5' nick-directed MMR in vitro could occur by an EXO1-independent mechanism, which involves strand displacement mediated by polymerase-δ, together with MutSα, MutLα, RPA, RFC and PCNA ( Figure 1D) [25]. Evidence from mammalian systems supporting the existence of EXO1-independent pathways in vivo is currently lacking.…”
Section: Repair Of Base/base Mismatches and Idlsmentioning
confidence: 99%